Collagen-Based Bioactive Bromelain Hydrolysate from Salt-Cured Cod Skin - Ezequiel R. Coscueta; María Emilia Brassesco; Manuela Pintado (Applied Sciences, 2021)
Considerable amounts of fish processing by-products are discarded each year. About 30% of this material may be skin and bone. Fish skin has more than 80% of its total protein content as collagen. Furthermore, in recent years, there has been a growing demand for collagen-based peptides due to their beneficial health effects. So, the objective of the present study was to optimise the obtaining bioactive hydrolysates from salt-cured cod skin using the protease Bromelain at 0.5% (w/w) concentration. This study developed a sustainable process that consumes less time and energy and uses an alternative source as raw material. In addition, bromelain allows hydrolysates with important antioxidant (ORAC, 514 μmol Trolox Equivalent/g protein) and antihypertensive activities (inhibition of ACE, IC50 of 166 μg protein/mL) as well as excellent biocompatibility with dermal and subcutaneous cells.